Religion and National Identity in Martyr Mutahhari’s View; an Analytical Review: Array - Qorbani, Qodratullah (Acta Universitatis Danubius. Communicatio, 2020)
Martyr Ayatollah Morteza Mutahhari is one of the Contemporary Iranian thinkers and intellectuals who tried to give a new definition of national identity. He believes that although there are some cultural, historical, racial, social and other factors that share in human’s identity, but the most significant factor is very religion and religious worldview that picture our tendencies to other aspects of life. In this case, Mutahhari thinks that for contemporary Muslim nations, like Iranians, the first factor of identity is the religion of Islam and the second is their geographical, national, cultural and racial factors. So, for Mutahhari, nationality is as the secondary but complementary factor for defining human identity. Regarding the role of Islam, Mutahhari’s pays more attention to the Quranic teachings, and the way of acceptance of Islam by Iranians. He believes that according to the Quran, holding theistic belief and religious faith is as the authentic criterion of our identity not belonging to a geographical nation. Concerning Iranian national identity, he refers to pre-Islamic Iran and the time of entering Islam to Iran, and studies Iranians national identity directly towards their submission to Islam, specially Shi’a school. So, his point of view concerning the relation of Islam and Iran, and historical importance of Islam in shaping Iranian identity has its special place and significance. In this, it is tried to analyze Mutahhari’s view concerning human identity and the role of religion in this case.